The Impact of Economic and Financial Management Practices on the Performance of Mexican Micro-Enterprises: A Multivariate Analysis - Ramírez-Urquidy, Martín A.; Aguilar-Barceló, José G.; Portal-Boza, Malena (Review of Business Management, 2018)
Purpose – The goal of this paper is to characterize the economic and financial management (EFM) practices in Mexican micro-enterprises and determine their impact on business performance under the hypothesis that EFM practices focused on achieving the optimal level of liquidity and profitability positively affect the performance of micro-enterprises. Design/methodology/approach – The study applies factor analysis,including both exploratory and confirmatory techniques, as well as linear regression models. Findings – The econometric analysis shows that both economic and financial management are statistically significant in explaining microenterprise performance, although only the effect of the latter is positive, whereas that of the former is negative. Originality/value – The paper’s findings could guide training and microcredit programs focused on micro-enterprise owners in developing countries and help to improve decision-making processes.